'Your Lovely Books': an author's view on celebrity. Issue 4 (1st October 2016) - Drabble, Margaret
ABSTRACT: The following piece by Margaret Drabble explores the tension between cultivating 'attention capital' (Rojek 2014, p. 456) through the practice and product of authorship and managing the demands of celebrity and public visibility. Drabble's apparent antipathy towards the material successes of 'celebrity' might be understood in terms of Leo Braudy's distinction between fame and celebrity. Braudy (1997, pp. 390–449) suggests that the spectre of 'celebrity' induces in the author of 'serious fiction' a 'posture of reticence and the sanction of neglect'. Drabble's performative, anonymous shuffling might therefore exemplify Braudy's (2011, p. 1072) axiom: 'To be neglected by the unthinking audience of the present guarantees future fame, and to be reticent similarly separates one from the crowd of aspiring braggarts'. Yet Drabble's performative ambivalence towards 'riches and glory', on the one hand, and the 'pleasure' readers take from her books, on the other, moves gradually towards an understanding of her own celebrity authorship as a positive facilitator of readers' attention – and company – on the 'lonely journey' of exploration she considers her work to be. Her close experience of how others live a relentlessly exposed life in the limelight also introduces an alternative, more practical, reason for relishing anonymity. In many ways, then, her text attests to the imbrication of the two gestures: the famous author 'turning away from us' and the celebrity author 'trying desperately to keep our attention' (Braudy and Boone 2011, p. 1072), and acknowledges a less clear-cut middle ground. What emerges, too, is a tension between the desire to write 'serious fiction' (and the importance of reading it), and the pleasures of being both entertained and the entertainer. Here, Drabble's thoughts demonstrate clearly how celebrity as a critical lens can unearth both ingrained beliefs and new conceptualisations about the social value of literature.